2021
DOI: 10.1038/s41598-021-98539-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of hyperbaric oxygen therapy for delayed neuropsychiatric sequelae after carbon monoxide poisoning

Abstract: To assess real-world effectiveness of hyperbaric oxygen therapy (HBOT) on delayed neuropsychiatric sequelae (DNS) after carbon monoxide (CO) poisoning we conducted a retrospective review of patients with CO poisoning admitted to Linkou Chang-Gung Memorial Hospital, Taiwan’s largest medical center, during 2009–2015. We included patients developing DNS after CO poisoning and compared improvements in neuropsychiatric function, with and without HBOT, after 12 months post-DNS to understand differences in recovery r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The optimal number of HBO therapy sessions for DNS remains unknown. However, additional sessions of HBO therapy for acute CO poisoning were considered sufficient to prevent subsequent poisoning 7,17 . In the present case, the patient received 89 sessions of HBO therapy, and his cognitive function continued to improve.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The optimal number of HBO therapy sessions for DNS remains unknown. However, additional sessions of HBO therapy for acute CO poisoning were considered sufficient to prevent subsequent poisoning 7,17 . In the present case, the patient received 89 sessions of HBO therapy, and his cognitive function continued to improve.…”
Section: Discussionmentioning
confidence: 69%
“…5 Hyperbaric oxygen (HBO) therapy is reportedly an effective treatment for DNS in the acute phase. [6][7][8] Predictive factors for favorable prognosis following HBO therapy include younger age, longer interictal periods, and independence in performing activities of daily living during intermittent CO poisoning. 9 However, the relationship between these factors and neuroimaging findings remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical evidence suggests hyperbaric oxygen therapy (HBOT) should be administered to all patients with CO intoxication to prevent the development of DNS [ 31 , 32 ]. Huang et al (2017) suggested that HBOT is associated with lower short- and long-term mortality in patients with significant CO poisoning, especially those with acute respiratory failure and patients younger than 20 years of age [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process allows a lot of dissolved oxygen to reach the bloodstream so that the cells' needs can be met by dissolved oxygen in the blood (16). In hyperbaric oxygen therapy, increasing the oxygen content of the blood (O 2 content) increases the transfer of oxygen from the blood to the tissues and facilitates the release of oxygen (17).…”
Section: Introductionmentioning
confidence: 99%